Uncertain trends in economic policy uncertainty - Nino Buliskeria; Jaromir Baxa; Tomáš Šestořád (Charles University in Prague, Institute of Economic Studies (IES), 2024)
The news-based Economic Policy Uncertainty indices (EPU) of Germany, France, and the United Kingdom display discernible trends that can be found neither in other European countries nor in other uncertainty indicators. Therefore, we replicate the EPU index of European countries and show that these trends are sensitive to the rather arbitrary choice of normalizing the raw counts of news related to economic policy uncertainty by the count of all newspaper articles. We show that an alternative normalization by news on economic policy leads to different long-term dynamics with less pronounced trends and markedly lower uncertainty during recent periods of uncertainty such as Brexit or the COVID-19 pandemic. Consequently, our results suggest that the effects of uncertainty related to these events on economic activity may have been overestimated.
Keywords: D80; E66; E32; 330; economic policy uncertainty; trend-cycle decomposition; reproducibility; reliability